Advancing nerve regeneration: translational perspectives of tacrolimus (FK506) - Däschler, Simeon C.; Feinberg, Konstantin; Harhaus-Wähner, Leila; Kneser, Ulrich; Gordon, Tessa; Borschel, Gregory H. (International journal of molecular sciences, 2023)
Peripheral nerve injuries have far-reaching implications for individuals and society, leading to functional impairments, prolonged rehabilitation, and substantial socioeconomic burdens. Tacrolimus, a potent immunosuppressive drug known for its neuroregenerative properties, has emerged in experimental studies as a promising candidate to accelerate nerve fiber regeneration. This review investigates the therapeutic potential of tacrolimus by exploring the postulated mechanisms of action in relation to biological barriers to nerve injury recovery. By mapping both the preclinical and clinical evidence, the benefits and drawbacks of systemic tacrolimus administration and novel delivery systems for localized tacrolimus delivery after nerve injury are elucidated. Through synthesizing the current evidence, identifying practical barriers for clinical translation, and discussing potential strategies to overcome the translational gap, this review provides insights into the translational perspectives of tacrolimus as an adjunct therapy for nerve regeneration.